Fear factor: The unseen perils of the Ebola outbreak. (2nd September 2016) - Shultz, James M.; Althouse, Benjamin M.; Baingana, Florence; Cooper, Janice L.; Espinola, Maria; Greene, M. Claire; Espinel, Zelde; McCoy, Clyde B.; Mazurik, Laurie; Rechkemmer, Andreas
ABSTRACT: As illustrated powerfully by the 2013–2016 Ebola outbreak in western Africa, infectious diseases create fear and psychological reactions. Frequently, fear transforms into action – or inaction – and manifests as "fear-related behaviors" capable of amplifying the spread of disease, impeding life-saving medical care for Ebola-infected persons and patients with other serious medical conditions, increasing psychological distress and disorder, and exacerbating social problems. And as the case of the US micro-outbreak shows, fear of an infectious-disease threat can spread explosively even when an epidemic has little chance of materializing. Authorities must take these realities into account if they hope to reduce the deadly effects of fear during future outbreaks.